ISOLASI DAN KARAKTERISASI PROTEASE DARI BAKTERI TANAH RAWA INDRALAYA, SUMATERA SELATAN [Isolation and Characterization of Proteases from Indralaya Soil Swamp Bacteria,South Sumatera] - Ace - Baehaki; Rinto - -; Arief - Budiman (Jurnal Teknologi dan Industri Pangan, 2011)
In an effort of obtaining indigenous protease producing bacteria, screening for bacterial protease was conducted from samples collected from Indralaya soil swamp, South Sumatera. Three of 31 colonies showed high protease activity with proteolytic index >1.00. T1S1 produced enzyme with the highest activity. The crude enzyme activity after 48 hours of incubation was 0.391 IU/ml. The optimum pH of the extracelull proteases from T1S1, T3S2 and T3S3 were 8.0, 8.0, and 7.5, respectively. The optimum temperature of T1S1, T3S2 and T3S3 proteases were 40, 50, and 500C, respectively. All metal ions tested (Na+, K+, Mn2+, Zn2+ and Fe2+) inhibited proteases except Fe2+ which activatesthe T3S3 protease at 5 mM. EDTA (1 and 5 mM) inhibited all proteases. Study on the effect of metals ion and spesific inhibitors indicated that all protease are metaloprotease. Molecular weights was determined using SDS-PAGE and zymogram technique. The molecular weight of T1S1 proteases was 121 kD,T3S2 proteaseswere 51, 71, and 119 kD whereas T3S3 proteaseswere 49, 70, and 116 kD.